The human brain book - Aldridge, Susan; Page, Martyn; Parker, Steve, 1952-; Frith, Christopher D.; Frith, Uta; Shulman, Melanie B. (London ; New York, N.Y. : DK Pub., 2009)
Combining the latest findings from the field of neuroscience with expert text and state-of-the-art illustrations, "The Human Brain Book" is a complete guide to the one organ in the body that makes each person a unique individual. Includes an interactive DVD.
No ordinary organ ; Investigating the brain ; Landmarks in neuroscience ; Scanning the brain ; A journey through the brain -- The brain and the body : Brain function ; Nervous system ; The brain and the nervous system ; Brain size, energy use, and protection ; Evolution -- Brain anatomy : Brain structures ; Brain zones and partitions ; Nuclei of the brain ; The thalamus, hypothalamus and pituitary gland ; The brainstem and cerebellum ; The limbic system ; The cerebral cortex ; Brain cells ; Nerve impulses -- The senses : How we sense the world ; The eye ; The visual cortex ; Visual pathways ; Visual perception ; Seeing ; The ear ; Making sense of sound ; Hearing ; Smell ; Perceiving smell ; Taste ; Touch ; The sixth sense ; Pain signals ; Experiencing pain -- Movement and control : Regulation ; The neuroendocrine system ; Planning a movement ; Executing a movement ; Unconscious action ; Mirror neurons -- Emotions and feelings : The emotional brain ; Conscious emotion ; Desire and reward -- The social brain : Sex, love, and survival ; Expression ; The self and others ; The moral brain -- Language and communication : Gestures and body language ; The origins of language ; The language areas ; A conversation ; Reading and writing -- Memory : The principles of memory ; The memory web ; Laying down a memory ; Recall and recognition ; Unusual memory -- Thinking : Intelligence ; Creativity and humor ; Belief and superstition ; Cognitive illusions -- Consciousness : What is consciousness? ; Locating consciousness ; Attention and consciousness ; Altering consciousness ; Sleep and dreams ; Time ; The self and consciousness -- The individual brain : Nature and nurture ; Influencing the brain ; Personality ; Strange brains -- Development and aging : The developing brain ; The aging brain ; The brain of the future -- Diseases and disorders : The disordered brain ; Directory of disorders -- Glossary.
DVD-ROM minimum system requirements, PC: Windows XP with service pack 2 or Windows Vista ; Intel or AMD processor ; soundcard ; 24-bit color display; screen resolution 1024 x 768.
DVD-ROM minimum system requirements, Macintosh: Mac OS X v10.4 ; G4, G5, or Intel processor ; soundcard ; 24-bit color display ; screen resolution 1024 x 768.
Keywords: CEREBRO -- FISIOLOGIA; NEUROFISIOLOGIA; ANORMALIDADES DEL CRANEO; ANATOMIA HUMANA